Cold Hardiness and Physio-Biochemical Responses of Annual Branches in Five Early-Fruiting Walnut Varieties (Juglans regia L.) Under Simulated Low-Temperature Stress - Zitong Ni; Haifang Hu; Guiqing Xu (Horticulturae)
As global climate change escalates, horticultural crops, especially walnuts, face increased vulnerability to frost damage. Cold hardiness—a crucial trait for survival—is influenced by complex physiological and biochemical mechanisms. This study assessed the cold hardiness of five walnut cultivars—‘Xinxin 2’, ‘Wen 81’, ‘Wen 185’, ‘Zha 343’, and ‘Xinzaofeng’—under simulated low-temperature stress, focusing on differences in freezing tolerance. One-year branches were gradually cooled to temperatures as low as −30 °C. Key physiological metrics, including electrolyte leakage (EL) and regrowth (RG) potential, along with biochemical metrics like antioxidant enzyme activities and osmoregulatory compounds, were used to evaluate cold hardiness. A comprehensive cold resistance indicator, derived using the subordination function method, highlighted cultivar resilience. Results showed significant variation in cold tolerance, with ‘Wen 185’ and ‘Wen 81’ exhibiting superior resilience, while ‘Xinxin 2’ was the most susceptible. Logistic regression analysis of relative electrolyte conductivity (REC) data estimated the semi-lethal temperature (LT50), identifying ‘Wen 81’ as the most cold-tolerant cultivar (LT50 = −21.73 °C). Antioxidant enzymes and osmoregulatory compounds were crucial for maintaining cellular stability and recovery after freezing. These findings offer practical insights for breeding cold-resistant cultivars and strategies to mitigate frost damage.